Municipal governments and forest management in Bolivia and Nicaragua - Kaimowitz, D.; Pacheco, P.; Mendoza, R.; Barahona, T. (Kluwer Academic Publishers, 2001)
This paper analyzes the growing role of municipal governments in Bolivia and Nicaragua in forest-related issues on the basis of some thirty case studies. It first provides background information on forest issues and legislation concerning municipal involvement in forest issues in the two countries. It then uses the case study material to derive some initial responses to six frequently asked questions about municipal forestry activities. It concludes that municipalities only devote a small proportion of their resources to these issues but show increasing interest and concern. Heavily forested municipalities tend to view forests as a productive asset, while the more deforested municipalities have greater concern for environmental degradation. Decentralization has opened opportunities for previously marginalized stakeholders to participate in forest policy decisions, but has not guaranteed that this will occur in every case. It has also favored local producers over outside interests. Inter-agency environmental commissions have achieved mixed results in Nicaragua. Municipalities implement a variety of forestry activities. However, the impact of increased municipal participation in forest issues on both forests and local livelihoods remains small compared to the magnitude of the problems. National government agencies, donor projects, NGOs, and community organizations could substantially improve these impacts in the future.